Das Konstrukt der bäuerlichen Kulturlandschaft Perspektiven von Landwirten im Schweizerischen Alpenraum - Stotten, Rike (alpine space - man and environment, 2015)
" The work explores the question of how cultural landscape is perceived or constituted by peasants and what role landscape socialization and habitus play in this process. Supported by the method of reflexive photography, an innovative approach to visual sociology, 28 farmers were interviewed in three communities in central Switzerland in individual interviews and group discussions. The results of the study show that farmers in their everyday use of the world construct the concept of cultural landscape from many aspects, but that are based primarily on the agricultural management of land. The results further extend the previous approach of landscape socialization and show that perception is strongly influenced by moral values."